2014
DOI: 10.1007/s00359-014-0906-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of dopamine in distal retina

Abstract: Dopamine is the most abundant catecholamine in the vertebrate retina. Despite the description of retinal dopaminergic cells three decades ago, many aspects of their function in the retina remain unclear. There is no consensus among the authors about the stimulus conditions for dopamine release (darkness, steady or flickering light) as well as about its action upon the various types of retinal cells. Many contradictory results exist concerning the dopamine effect on the gross electrical activity of the retina [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 243 publications
1
56
1
Order By: Relevance
“…The pathogenesis of PD involves the progressive degeneration of dopaminergic neurons and dopamine (DA) depletion in the nigrostriatal system. Dopaminergic neurons were identified in the neural retina as amacrine and interplexiform cells (Frederick et al, 1982) (Popova, 2014). Therefore, the distribution of one of the two enzymes involved in DA synthesis, tyrosine hydroxylase (TH), was also analyzed in both control and DJ-1 KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenesis of PD involves the progressive degeneration of dopaminergic neurons and dopamine (DA) depletion in the nigrostriatal system. Dopaminergic neurons were identified in the neural retina as amacrine and interplexiform cells (Frederick et al, 1982) (Popova, 2014). Therefore, the distribution of one of the two enzymes involved in DA synthesis, tyrosine hydroxylase (TH), was also analyzed in both control and DJ-1 KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is worth noting that the visual signal processes must be altered in KO mice as dopamine plays an important and extensive modulatory role in the vertebrate visual system. 26,40 Reported and observed effects of D1Rs and D2Rs on the ERGs seem to be contradictory. Pharmacologic blockade or genetic mutation of D2Rs in this study slightly increased b-wave and summed OP amplitudes, which are similar to the effects mediated by D2R antagonists in goldfish 41 …”
Section: Discussionmentioning
confidence: 99%
“…25 Studies based on autoradiography and immunohistochemistry found that horizontal, bipolar, amacrine, and ganglion cells express mainly D1-like receptors, whereas photoreceptors express D2 receptors. 26 Similar to dopamine, the affinity of APO for D2 receptors (D2Rs) is up to 22-fold greater than for D1 receptors (D1Rs). 27 An important step in evaluating the involvement of dopamine signaling in refractive development and eye growth is to determine the specific type of dopamine receptors involved.…”
mentioning
confidence: 99%
“…A number of factors control spinule formation including dopamine and protein kinase C (reviewed in Wagner and Djamgoz 1993; Popova 2014), as well as nerve growth factor (Haamedi et al 2001) and retinoic acid (Dirks et al 2004). Spinules may mediate “
feedback activity essential for the coding of antagonistic color information” (Popova 2014). Some believe that the spinules mediate a subset of postsynaptic responses, as they possess structures similar to PSDs.…”
Section: Synaptic/neuronal Invaginating Projections In More Complex Amentioning
confidence: 99%